Overcoming high-temperature strength-ductility trade-off by combination deformation twinning of C11b and D022 superlattices in a Ni-Cr-W/Mo-based superalloy. (November 2022) - Li, Xiaolin; He, Yi; Liu, Linxi; Gao, Xiangyu; Hua, Ke; Wang, Haifeng
Abstract: A Ni-7.9Cr-5.9W-22.2Mo-1.4Ti (wt.%) superalloy was designed and prepared to have simultaneously high densities of nanoscale C11b and D022 superlattices within the disordered Ni-based austenite matrix. As a result, both strength and ductility were enhanced significantly at the elevated temperature as compared to the Ni-8Cr-6W-22.5Mo superalloy with only the nanoscale C11b superlattice. This is ascribed to not only co-existent precipitation strengthening of nanoscale C11b and D022 superlattices but also their combination deformation twinning induced strength and plasticity. Such a novel mechanism to overcome high-temperature strength-ductility trade-off would shed some light on designing advanced Ni-based superalloys. Graphical abstract: Image, graphical abstract